Tiền tố và kết quả của sự gắn kết của nhân viên với thương hiệu công ty - Kiều Anh , Tài; Trần Khải , Hoàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research aims to investigate the impact of internal branding dimensions on employee-corporate brand engagement, and ultimately employee loyalty, brand-related positive word-of-mouth, and work performance. The survey was conducted with frontline employees of service firms in Ho Chi Minh City. After being screened, the usable data including 300 samples were analyzed using the PLS-SEM method. Results revealed that two of three internal branding dimensions, which are brand communication and brand leadership, affect positively and significantly employee-corporate brand engagement. Findings also showed that employee-corporate brand engagement influences positively and significantly employee loyalty, corporate brand-related positive word-of-mouth, and work performance.
Keywords: Brand engagement; Internal branding; Brand communication; Brand leadership; Corporate brand